1998
DOI: 10.1084/jem.187.10.1623
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Selection by Epidermal Dendritic Cells during Transmission across Human Skin

Abstract: Macrophage tropic HIV-1 is predominant during the initial viremia after person to person transmission of HIV-1 (Zhu, T., H. Mo, N. Wang, D.S. Nam, Y. Cao, R.A. Koup, and D.D. Ho. 1993. Science. 261:1179–1181.), and this selection may occur during virus entry and carriage to the lymphoid tissue. Human skin explants were used to model HIV-1 selection that may occur at the skin or mucosal surface. Macrophage tropic, but not T cell line tropic strains of HIV-1 applied to the abraded epidermis were recovered from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
123
1
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(140 citation statements)
references
References 50 publications
(75 reference statements)
15
123
1
1
Order By: Relevance
“…Several studies have demonstrated that LC infection with R5-tropic HIV-1 is essential to its role in transmission [34][35][36][37]. However, recently it was shown that mature CD34 1 -derived LC-like cells can transmit HIV-1 without infection [38].…”
Section: Subsets In Hiv-1 Transmissionmentioning
confidence: 99%
“…Several studies have demonstrated that LC infection with R5-tropic HIV-1 is essential to its role in transmission [34][35][36][37]. However, recently it was shown that mature CD34 1 -derived LC-like cells can transmit HIV-1 without infection [38].…”
Section: Subsets In Hiv-1 Transmissionmentioning
confidence: 99%
“…DC-SIGN interacts with the envelope glycoprotein gp120 of HIV-1, HIV-2, and SIV (3)(4)(5)(6)(7)(8), as well as other pathogens such as hepatitis C (9, 10), Ebola (11), cytomegalovirus (12), Dengue virus (13), Mycobacterium (14)(15)(16), Leishmania (17,18), Candida albicans (19), and Helicobacter pylori (20,21). DC-SIGN has been implicated as playing an important role in HIV-1 transmission and the establishment of infection (4,6,(22)(23)(24)(25). The interaction of HIV-1 with DC-SIGN can lead to infection of the DCs, or alternatively the virus can be internalized into a trypsin-resistant compartment prior to undergoing transfer to its main target cells, and this mechanism has been shown to greatly enhance infection of T cells in vitro (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…Although they do not express DC-SIGN, LCs express CD4 and HIV chemokine coreceptors, and these molecules have been shown to mediate infection of LCs (11)(12)(13)(14). Immature LCs express surface CCR5, but not surface CXCR4, immediately after isolation from skin; CCR5 on LCs also mediates fusion with cells expressing the HIV envelope protein gp120 (11).…”
mentioning
confidence: 99%